Allegory and Ethics in Beethoven’s Fidelio - Rumph, Stephen (Les Cahiers de la Société québécoise de recherche en musique, 2010)
Few operas foreground ethics as clearly as Beethoven’s Fidelio. Yet the heroic tale of liberation from political oppression resists narrowly historical interpretations, availing itself equally to revolutionary and reactionary interpretations. Allegory theory offers a new approach to the ethical meanings of Fidelio. Allegory, in which characters embody moral qualities, preserved a hierarchical and theocentric view of society, in opposition to the humanistic outlook of Enlightenment mimesis. Allegory and mimesis coexist in Fidelio, whose title character traces a lineage to the Christian morality play. This essay compares the 1805 original of Beethoven’s opera (Leonore) with the 1814 version (Fidelio), concentrating on the final scene and the character of Marzelline. I argue that the 1814 version enhances the allegorical dimension, simplifying the characters and reducing moral complexities. Fidelio models the traditional “consensus society” of pre-Revolutionary Europe, offering a vision congenial to Congress of Vienna audiences.